Green low-cost high-performance radiation heat dissipation coating and preparation method thereof

By using the radiation heat dissipation coating prepared by functional fillers and binders, the problem of low daytime temperature reduction efficiency in the prior art is solved, and an efficient and low-cost heat dissipation effect is achieved.

CN119592118APending Publication Date: 2025-03-11SHENZHEN RES INST OF SHANGHAI JIAOTONG UNIV +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311158626.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing radiation heat dissipation technology is difficult to effectively reduce the temperature of objects during the day, and the preparation process of traditional heat dissipation coatings is complex and costly, making it difficult to apply on a large scale.

Method used

Radiation heat dissipation coatings composed of functional fillers (such as diatomaceous earth) and binders (such as methylcellulose), and coatings with high solar reflectivity and high infrared emissivity are prepared through high temperature sintering and magnetic stirring.

Benefits of technology

It achieves efficient reduction of object temperature during the day, and is simple in process and low in cost, making it suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a radiation heat dissipation coating and a preparation method thereof. Preferably, the coating comprises the following components: methyl cellulose with a strong radiation characteristic in a wave band of 8-14 microns and diatomite with a strong reflection characteristic in a wave band of 0.25-2.5 microns and a strong emission characteristic in a wave band of 8-14 microns. The reflectivity of the coating in the visible near-infrared band (0.25-2.5 microns) reaches 92% or above, and the emissivity of the coating in the middle-infrared band (8-14 microns) can reach 0.88 or above. The radiation heat dissipation coating disclosed by the invention is excellent in performance, simple in preparation process and low in cost, deionized water can be independently selected as a solvent, preparation of a non-toxic and environment-friendly coating is completely realized, the coating can be coated on different substrate surfaces such as wood boards, cement wall surfaces, metal, glass, ceramics and plastics, and green and energy-consumption-free heat dissipation is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field, and in particular to a green, low-cost, high-performance radiation heat dissipation coating and a preparation method thereof. Background Art

[0002] According to the World Meteorological Organization (WMO), as one of the main greenhouse gases, the concentration of carbon dioxide (CO2) has reached 149% of the pre-industrial level. If greenhouse gas emissions continue to grow at a high rate, the temperature rise by the end of this century is expected to be far greater than we expected. One of the main contributions to carbon dioxide emissions is energy consumption in residential buildings. The main end-use categories of energy consumption in residential buildings include space heating and cooling, lighting, etc. Driven by the dual goals of saving non-renewable energy and slowing down the rise in temperature, countries around the world have taken various measures to improve energy efficiency and carbon dioxide emissions.

[0003] Among the sources of global greenhouse gas emissions, emissions caused by energy use account for 73%, and carbon emissions from building energy consumption account for nearly 40%, of which building thermal control energy consumption accounts for about 60%. Thermal control energy consumption is one of the main sources of greenhouse gas emissions. Therefore, when designing thermal control systems, energy-saving design should be given an important position. Cooling is an indispensable part of human production and life. With the improvement of quality of life, people's cooling needs will become higher and higher. Cooling technology is needed in many places such as building exterior surfaces and electronic heating devices. Traditional cooling equipment consumes a lot of non-renewable energy and causes greenhouse gas emissions. Therefore, it is of great significance to develop new green cooling technology.

[0004] In the past decade, the energy consumption of cooling equipment has increased significantly. As global warming continues, the demand for cooling is expected to rise further, making the development of a low-energy cooling technology urgent. Compared with most traditional technologies that reduce temperature through energy consumption, radiative cooling is an environmentally friendly and energy-free cooling technology that reflects sunlight and emits heat into outer space in the form of infrared radiation. Therefore, the development and application of radiative cooling technology is of great significance to achieving energy sustainable development and mitigating global temperature rise and climate change.

[0005] Passive radiation cooling is an environmentally friendly, energy-free cooling technology that achieves cooling by reflecting solar radiation and radiating the heat of objects into outer space. The heat of an object mainly comes from solar thermal radiation, thermal radiation from surrounding objects, thermal convection and thermal conduction, etc. At the same time, an object can also radiate heat outward in the form of thermal radiation. Therefore, in order to achieve the purpose of cooling by radiation, it is key to reduce solar radiation absorption and increase its own thermal emission, that is, to have as high a reflectivity as possible in the sunlight band (0.25-2.5μm) to absorb the least energy, and to have as high an emissivity as possible in the atmospheric window band (8-14μm) to radiate more energy.

[0006] Radiative cooling technology was proposed as early as the 1950s and 1960s and was widely used in the research of nighttime cooling. However, since objects absorb more heat in the sun, the cooling demand during the day is much more important than at night. In order to achieve the purpose of heat dissipation, higher requirements are placed on the radiator. For a long time, researchers have not found a method that can meet both the high reflectivity in the solar band and the high emissivity in the infrared region. The results achieved can only reduce the temperature rise of objects during the day, but cannot achieve the goal of being below the ambient temperature. Therefore, for decades, radiative cooling has been limited to the field of nighttime cooling. Until Raman et al. (Nature, 2014, 515: 540-544) proposed a multilayer photonic structure radiant heat sink, the solar reflectivity could reach 97%, with excellent performance. However, the preparation process of this type of photonic structure heat sink is complicated and costly, making it difficult to apply on a large scale. Zhai et al. (Science, 2017, 355 (6329): 1062-1066) prepared a radiant heat dissipation film by randomly dispersing SiO2 microspheres in an organic matrix material. When silver is used as a backing, the film can reflect 96% of solar radiation and has an emissivity of more than 93% in the 8-14 μm band. However, this type of heat sink is difficult to cover the surface of irregular objects, so it is also difficult to use in practice. In terms of radiant heat dissipation coatings, currently commonly used fillers such as titanium dioxide, aluminum oxide, and silicon dioxide all have certain defects. For example, titanium dioxide has a certain absorption in the ultraviolet band, resulting in a low solar reflectivity in this band, while microspheres of alumina and silicon dioxide with specific diameters are relatively expensive, so it is impossible to achieve both excellent performance and low cost at the same time.

[0007] In the existing heat dissipation coating preparation technology, it is usually necessary to add a variety of additives to achieve the purposes of leveling, adhesion, dispersion, and defoaming, which increases the preparation and use costs and is not conducive to the sustainable development of the environment. The present invention only needs to use functional fillers and adhesives with centrifugal defoaming mechanical equipment to achieve the preparation of the heat dissipation coating without adding various additives.

[0008] The Chinese patent with publication number CN103965672A discloses a coating for heat dissipation on the surface of LED heat sink with strong adhesion, which uses nano-diatomite as one of the raw materials of the coating to provide the coating with excellent surface properties, volume increase, thickening and improved adhesion. However, nano-level diatomite needs to undergo a more complicated process, which increases the production cost of the coating.

[0009] The Chinese patent with publication number CN103555040A discloses a nano coating on the surface of an EVA film, which uses carboxymethyl cellulose as a binder. However, carboxymethyl cellulose has poor water solubility. When added to the coating as a binder, it may peel off and crack when used in humid conditions in real life. Summary of the invention

[0010] The present invention aims at the deficiencies of the prior art and provides a green, low-cost, high-performance radiation heat dissipation coating and a preparation method thereof. The radiation heat dissipation coating has the characteristics of high solar reflectivity, high atmospheric window emissivity, green and non-toxic, simple preparation and low cost.

[0011] The present invention is achieved through the following technical solutions:

[0012] The present invention provides a green, low-cost, high-performance radiation heat dissipation coating, which is prepared from the following components and raw materials in parts by weight:

[0013] 4-15 parts of functional filler;

[0014] 1 part of adhesive;

[0015] 5-100 parts of solvent.

[0016] Preferably, the functional filler comprises diatomaceous earth, and the particle size of the diatomaceous earth is 1-15 μm and the pore size is 10-500 nm.

[0017] Preferably, the functional filler also includes one or more of calcium carbonate, barium sulfate, titanium dioxide, silicon dioxide, and aluminum oxide.

[0018] Preferably, the binder comprises methylcellulose.

[0019] As another embodiment of the present invention, the binder further comprises one or more of polyvinylidene fluoride, cellulose acetate, ethyl cellulose, acrylic resin, and polydimethylsiloxane.

[0020] As another embodiment of the present invention, the solvent includes one or more of deionized water, N,N-dimethylformamide, N,N-dimethylacetamide, acetone, and anhydrous ethanol.

[0021] The present invention also provides a method for preparing the above radiation heat dissipation material, comprising the following steps:

[0022] S1, sintering the functional filler at high temperature;

[0023] S2, adding a binder to a solvent and stirring to obtain a solution;

[0024] S3, adding the functional filler into the solution in step S2;

[0025] S4. After stirring and removing bubbles, the radiant heat dissipation coating is obtained.

[0026] Preferably, the high temperature sintering method in step S1 includes: high temperature sintering in a muffle furnace, the sintering temperature is 450-1200° C., and the sintering time is 4-12 hours.

[0027] Preferably, the stirring method in step S2 includes magnetic stirring, with a rotation speed of 400-1300 r / min and a stirring time of 4-12 h.

[0028] Preferably, the mass ratio of the binder to the solvent in step S2 is 1:5-100, and the mass ratio of the functional filler to the binder in step S3 is 4-15:1.

[0029] Preferably, after adding the functional filler into the solution in step S2 in step S3, stirring is further performed, and the stirring method includes magnetic stirring, the rotation speed is 500-1300 r / min, and the stirring time is 1-12 h.

[0030] Preferably, the stirring and defoaming method in step S4 includes using a centrifugal defoaming mixer for stirring and defoaming, the rotation speed of the centrifugal defoaming mixer is 1000-2000 rpm, and it runs in stirring mode for 5-20 minutes and defoaming mode for 5-20 minutes respectively.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) The preferred functional filler diatomite of the present invention is a material existing in nature. Compared with the traditional radiation cooling silica spheres, it has the advantages of low price and simple preparation. At the same time, diatomite has a hierarchical porous structure. Its micron-level size and nanometer-level holes reflect the light of the corresponding band, thereby improving the reflectivity of the solar (0.25-2.5 μm) band. The main component of diatomite is silicon dioxide, which has a vibration peak in the atmospheric window band and has high emissivity, providing natural favorable conditions for high reflectivity in the 0.25-2.5 μm band and high emissivity in the 8-14 μm band.

[0033] (2) The preferred binder methyl cellulose of the present invention can be dissolved by deionized water combined with centrifugal stirring, and no volatile organic solvents are used in the whole process of coating preparation, which has the advantages of green recycling, environmental friendliness, simple preparation, and low cost;

[0034] (3) The binder methylcellulose of the present invention can improve the water solubility of the coating to a certain extent, and can also maintain good bonding performance under humid conditions. In addition, methylcellulose has an absorption peak in the atmospheric window band (8-14 μm), which can assist diatomaceous earth and other functional fillers in producing a high emissivity effect;

[0035] (4) The diatomaceous earth used in the radiant heat dissipation coating of the present invention is micron-level diatomaceous earth, which has a lower acquisition cost than the nano-diatomaceous earth in the prior art. The high-temperature roasting process is used to improve the purity of the diatomaceous earth and remove impurities. The roasting of the diatomaceous earth can remove organic impurities in the diatomaceous earth and increase the content of silicon dioxide, an effective ingredient in the diatomaceous earth. The roasting can also remove the diatomaceous earth covering the pores of the diatomaceous earth, so that the pores of the diatomaceous earth are exposed, thereby improving the reflectivity to the sunlight band.

[0036] (5) The radiant heat dissipation coating of the present invention is applied to the surface of the substrate. Diatomaceous earth and other functional fillers provide good hiding power. The good bonding property of methyl cellulose can provide primary adhesion. It has excellent practicality in real scenes. The coating can be applied to different substrate surfaces such as wood boards, cement walls, metals, glass, ceramics, and plastics to achieve green and energy-free heat dissipation, which complies with the provisions of the national standards GB30981-2020 "Limits of Hazardous Substances in Industrial Protective Coatings", GB24409-2020 "Limits of Hazardous Substances in Vehicle Coatings", and GB / T18178-2000 "General Rules for the Selection of Waterborne Coating Systems".

[0037] (6) The radiant heat dissipation coating of the present invention is composed of a binder with strong radiation properties in the 8-14μm band and a functional filler with high reflectivity in the 0.25-2.5μm band and high emissivity in the 8-14μm band. The coating has a reflectivity of 90% in the ultraviolet, visible and near-infrared bands (0.25-2.5μm) and an emissivity of 0.9 in the mid-infrared atmospheric window band (8-14μm). DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0039] The diatomaceous earth used in the examples of the present invention was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0040] The magnetic stirrer used in the embodiments of the present invention is a common magnetic stirrer purchased from Changsha Miqi Instrument Equipment Co., Ltd.

[0041] The centrifugal defoaming mixer used in the embodiment of the present invention is a 300D centrifugal defoaming mixer purchased from Shenzhen Defeng Mixing Technology Co., Ltd. The centrifugal defoaming mixer can mix the substances more evenly, remove bubbles and air, and reduce the use of additives such as defoaming agents, thereby ensuring the water solubility of the heat dissipation coating.

[0042] Example 1

[0043] The functional filler used in this embodiment is diatomite, the particle size of the diatomite is 1-15 μm, the pore size range is 10-500 nm, the binder used is methyl cellulose, and the solvent used is deionized water. A green non-toxic radiation heat dissipation coating and its preparation method include the following steps:

[0044] (a) sintering diatomite at 1200°C for 4 h in a muffle furnace;

[0045] (b) 0.2 g of methylcellulose was added to 17.5 mL of deionized water and stirred at 500 rpm for 12 h using a magnetic stirrer to obtain a transparent solution;

[0046] (c) 1.5 g of calcined diatomaceous earth was weighed and added to the above transparent solution. The magnetic stirring was continued at 1300 rpm for 2 h to obtain a mixed solution. The mixed solution was then placed in a centrifugal defoaming mixer and operated in a stirring mode at a speed of 1500 rpm for 15 min. Then, the mixture was operated in a defoaming mode at a speed of 1500 rpm for 15 min. Thus, the radiant heat dissipation coating was obtained.

[0047] The radiation heat dissipation coating was evenly applied to the acrylic plate and air-dried. Lambda 950 UV-Vis-NIR spectrophotometer and Nicolet 6700 infrared integrating sphere Fourier transform infrared spectrometer were used to measure the reflectivity of the coating in the solar band and the emissivity in the mid-infrared band according to the instructions. The results showed that the reflectivity of the coating with a thickness of 450μm in the solar band (0.25-2.5μm) was 94%, and the emissivity in the atmospheric window band (8-14μm) was 0.9. After the roof cooling experiment test, when the coating was applied to the surface of the object at noon in direct sunlight in winter, the acrylic plate with the heat dissipation coating was placed on the roof. By recording the sample and ambient temperature for 24 hours without interruption, it was detected that the sample temperature could reach 6℃ lower than the ambient temperature.

[0048] Example 2

[0049] The functional filler used in this embodiment is diatomite, the particle size of the diatomite is 1-15 μm, the pore size range is 10-500 nm, the binder used is methyl cellulose, and the solvent used is deionized water. A green non-toxic radiation heat dissipation coating and its preparation method include the following steps:

[0050] (a) sintering diatomite at 950°C for 8 hours in a muffle furnace;

[0051] (b) 0.2 g of methylcellulose was added to 17.5 mL of deionized water and stirred at 1300 rpm for 4 h using a magnetic stirrer to obtain a transparent solution;

[0052] (c) 1.4 g of calcined diatomaceous earth was weighed and added to the above transparent solution. The magnetic stirring was continued at 500 rpm for 12 h to obtain a mixed solution. The mixed solution was then placed in a centrifugal defoaming mixer and operated in a stirring mode at a speed of 1500 rpm for 15 min. Then, the mixture was operated in a defoaming mode at a speed of 1500 rpm for 10 min to obtain a radiant heat dissipation coating.

[0053] The radiant heat dissipation coating was evenly applied to the steel plate and air-dried. The reflectivity of the coating in the solar band and the emissivity in the mid-infrared band were measured using a Lambda 950 UV-Vis-NIR spectrophotometer and a Nicolet 6700 infrared integrating sphere Fourier transform infrared spectrometer according to the instructions. The results showed that the reflectivity of the coating with a thickness of 450 μm in the solar band (0.25-2.5 μm) was 93%, and the emissivity in the atmospheric window band (8-14 μm) was 0.89.

[0054] Example 3

[0055] The functional filler used in this embodiment is diatomite, the particle size of the diatomite is 1-15 μm, the pore size range is 10-500 nm, the binder used is methyl cellulose, and the solvent used is deionized water. A green non-toxic radiation heat dissipation coating and its preparation method include the following steps:

[0056] (a) sintering diatomite at 450° C. for 12 h in a muffle furnace for later use;

[0057] (b) 0.2 g of methylcellulose was added to 17.5 mL of deionized water and stirred with a magnetic stirrer at 800 rpm for 8 h to obtain a transparent solution;

[0058] (c) 1.3 g of calcined diatomaceous earth was weighed and added to the above transparent solution. The magnetic stirring was continued at 1000 rpm for 2 h to obtain a mixed solution. The mixed solution was then placed in a centrifugal defoaming mixer and operated in a stirring mode at a speed of 1500 rpm for 15 min. Then, the mixture was operated in a defoaming mode at a speed of 1500 rpm for 15 min. Thus, the radiant heat dissipation coating was obtained.

[0059] The radiant heat dissipation coating was evenly applied on a copper plate and air-dried. The reflectivity of the coating in the solar band and the emissivity in the mid-infrared band were measured using a Lambda 950 UV-Vis-NIR spectrophotometer and a Nicolet 6700 infrared integrating sphere Fourier transform infrared spectrometer according to the instructions. The results showed that the reflectivity of the coating with a thickness of 450 μm in the solar band (0.25-2.5 μm) was 92%, and the emissivity in the atmospheric window band (8-14 μm) was 0.88.

[0060] Example 4

[0061] The functional fillers used in this embodiment are diatomaceous earth and calcium carbonate, the particle size of the diatomaceous earth is 1-15 μm, the pore size range is 10-500 nm, the binder used is methyl cellulose, and the solvent used is deionized water. A low-cost radiation heat dissipation coating and a preparation method thereof include the following steps:

[0062] (a) sintering diatomite at 1200°C for 4 h in a muffle furnace;

[0063] (b) 0.2 g of methylcellulose was added to 17.5 mL of deionized water and stirred at 400 rpm for 12 h using a magnetic stirrer to obtain a transparent solution;

[0064] (c) 3 g of calcium carbonate and 3 g of calcined diatomaceous earth were weighed and added to the above transparent solution, and magnetic stirring was continued at 1200 rpm for 1 hour to obtain a mixed solution. The mixed solution was then placed in a centrifugal defoaming mixer and operated in a stirring mode at a speed of 1000 rpm for 15 minutes, and then operated in a defoaming mode at a speed of 1000 rpm for 20 minutes to obtain a radiant heat dissipation coating.

[0065] The radiant heat dissipation coating was evenly applied on the glass and air-dried. The reflectivity of the coating in the solar band and the emissivity in the mid-infrared band were measured using a Lambda 950 UV-Vis-NIR spectrophotometer and a Nicolet 6700 infrared integrating sphere Fourier transform infrared spectrometer according to the instructions. The results showed that the reflectivity of the coating with a thickness of 800 μm in the solar band (0.25-2.5 μm) was 96%, and the emissivity in the atmospheric window band (8-14 μm) was 0.93.

[0066] Example 5

[0067] The functional fillers used in this embodiment are diatomaceous earth and barium sulfate, the particle size of the diatomaceous earth is 1-15 μm, the pore size range is 10-500 nm, the binder used is methyl cellulose, and the solvent used is deionized water. A low-cost radiant heat dissipation coating and a preparation method thereof include the following steps:

[0068] (a) sintering diatomite at 1200°C for 4 h in a muffle furnace;

[0069] (b) 0.2 g of methylcellulose was added to 17.5 mL of deionized water and stirred at 600 rpm for 10 h using a magnetic stirrer to obtain a transparent solution;

[0070] (c) 3 g of barium sulfate and 3 g of calcined diatomaceous earth were weighed and added to the above transparent solution, and magnetic stirring was continued at 700 rpm for 10 h to obtain a mixed solution. The mixed solution was then placed in a centrifugal defoaming mixer and operated in a stirring mode at a speed of 2000 rpm for 5 min, and then operated in a defoaming mode at a speed of 2000 rpm for 5 min, to obtain a radiant heat dissipation coating.

[0071] The radiant heat dissipation coating was evenly applied to the steel plate and air-dried. The reflectivity of the coating in the solar band and the emissivity of the mid-infrared band were measured using a Lambda 950 UV-Vis-NIR spectrophotometer and a Nicolet 6700 infrared integrating sphere Fourier transform infrared spectrometer according to the instructions. The results showed that the reflectivity of the coating with a thickness of 800 μm in the solar band (0.25-2.5 μm) was 97%, and the emissivity in the atmospheric window band (8-14 μm) was 0.92.

[0072] Example 6

[0073] The functional fillers used in this embodiment are diatomaceous earth and titanium dioxide, the particle size of the diatomaceous earth is 1-15 μm, the pore size range is 10-500 nm, the binder used is methyl cellulose, and the solvent used is deionized water. A low-cost radiant heat dissipation coating and a preparation method thereof include the following steps:

[0074] (a) sintering diatomite at 1200°C for 4 h in a muffle furnace;

[0075] (b) 0.2 g of methylcellulose was added to 17.5 mL of deionized water and stirred with a magnetic stirrer at 900 rpm for 6 h to obtain a transparent solution;

[0076] (c) Weigh 2 g of titanium dioxide and 3 g of calcined diatomaceous earth and add them to the above transparent solution, continue magnetic stirring at 600 rpm for 8 hours to obtain a mixed solution, then put the mixed solution into a centrifugal defoaming mixer, first run it in a stirring mode at a speed of 1200 rpm for 15 minutes, and then run it in a defoaming mode at a speed of 1200 rpm for 15 minutes, to obtain a radiant heat dissipation coating.

[0077] The radiant heat dissipation coating was evenly applied on the acrylic plate and air-dried. The reflectivity of the coating in the solar band and the emissivity in the mid-infrared band were measured using a Lambda 950 UV-Vis-NIR spectrophotometer and a Nicolet 6700 infrared integrating sphere Fourier transform infrared spectrometer according to the instructions. The results showed that the reflectivity of the coating with a thickness of 800 μm in the solar band (0.25-2.5 μm) was 93%, and the emissivity in the atmospheric window band (8-14 μm) was 0.92.

[0078] Comparative Example 1

[0079] The difference between this comparative example and Example 1 is that carboxymethyl cellulose is used as a binder.

[0080] The radiation heat dissipation coating was evenly applied to the acrylic plate and air-dried. Lambda 950 UV-visible-near infrared spectrophotometer and Nicolet 6700 infrared integrating sphere Fourier transform infrared spectrometer were used to measure the reflectivity of the coating in the solar band and the emissivity in the mid-infrared band according to the instructions. The results showed that the reflectivity of the coating with a thickness of 450μm in the solar band (0.25-2.5μm) was 89%, and the emissivity in the atmospheric window band (8-14μm) was 0.80. After the roof cooling experiment test, when the coating was applied to the surface of the object at noon in direct sunlight in winter, the acrylic plate with the heat dissipation coating was placed on the roof. By recording the sample and ambient temperature for 24 hours without interruption, the sample temperature could only reach 4℃ lower than the ambient temperature.

[0081] Comparative Example 2

[0082] The difference between this comparative example and Example 1 is that the high temperature sintering process is not included.

[0083] The radiation heat dissipation coating was evenly applied to the acrylic plate and air-dried. Lambda 950 UV-Vis-NIR spectrophotometer and Nicolet 6700 infrared integrating sphere Fourier transform infrared spectrometer were used to measure the reflectivity of the coating in the solar band and the emissivity in the mid-infrared band according to the instructions. The results showed that the reflectivity of the coating with a thickness of 450μm in the solar band (0.25-2.5μm) was 89%, and the emissivity in the atmospheric window band (8-14μm) was 0.87. After the roof cooling experiment test, when the coating was applied to the surface of the object at noon in direct sunlight in winter, the acrylic plate with the heat dissipation coating was placed on the roof. By recording the sample and ambient temperature for 24 hours without interruption, the sample temperature could only reach 3℃ lower than the ambient temperature.

[0084] Comparative Example 3

[0085] The difference between this comparative example and Example 1 is that nano-diatomite is used as the functional filler, the particle size of the nano-diatomite is in the range of 100-200 nm, and most of the pore sizes are about 5 nm.

[0086] The radiation heat dissipation coating was evenly applied to the acrylic plate and air-dried. Lambda 950 UV-visible-near infrared spectrophotometer and Nicolet 6700 infrared integrating sphere Fourier transform infrared spectrometer were used to measure the reflectivity of the coating in the solar band and the emissivity in the mid-infrared band according to the instructions. The results showed that the reflectivity of the coating with a thickness of 450 μm in the solar band (0.25-2.5 μm) was 90%, and the emissivity in the atmospheric window band (8-14 μm) was 0.82. After the roof cooling experiment test, when the coating was applied to the surface of the object at noon in direct sunlight in winter, the acrylic plate with the heat dissipation coating was placed on the roof. By recording the sample and ambient temperature for 24 hours without interruption, the sample temperature could only reach 4.5℃ lower than the ambient temperature.

[0087] Comparative Example 4

[0088] The difference between this comparative example and Example 6 is that only titanium dioxide is used as the filler.

[0089] The radiation heat dissipation coating is evenly applied to the acrylic plate and air-dried. Lambda 950 UV-visible-near infrared spectrophotometer and Nicolet 6700 infrared integrating sphere Fourier transform infrared spectrometer are used to measure the reflectivity of the coating in the solar band and the emissivity of the mid-infrared band respectively according to the method in the manual. The measurement results show that the reflectivity of the coating with a thickness of 800 μm in the solar band (0.25-2.5 μm) is 88%, and the emissivity in the atmospheric window band (8-14 μm) is 0.81. Therefore, when only titanium dioxide is used as a filler, titanium dioxide has a certain absorption in the ultraviolet band, resulting in a low solar reflectivity in this band. After adding diatomaceous earth in Example 6, the hierarchical porous structure of diatomaceous earth and the particle size of silicon dioxide widen the reflection band, make up for the absorption loss of silicon dioxide in the ultraviolet band, and greatly improve the reflectivity of the ultraviolet visible near infrared band (0.25-2.5 μm).

[0090] Comparative Example 5

[0091] The difference between this comparative example and Example 1 is that the particle size of the diatomaceous earth used is 1-15 μm, and most of the pore sizes are 1-3 μm.

[0092] The radiation heat dissipation coating was evenly applied to the acrylic plate and air-dried. Lambda 950 UV-visible-near infrared spectrophotometer and Nicolet 6700 infrared integrating sphere Fourier transform infrared spectrometer were used to measure the reflectivity of the coating in the solar band and the emissivity in the mid-infrared band according to the instructions. The results showed that the reflectivity of the coating with a thickness of 450μm in the solar band (0.25-2.5μm) was 86%, and the emissivity in the atmospheric window band (8-14μm) was 0.87. After the roof cooling experiment test, when the coating was applied to the surface of the object at noon in direct sunlight in winter, the acrylic plate coated with the heat dissipation coating was placed on the roof. By recording the sample and ambient temperature for 24 hours without interruption, the sample temperature could only reach 2°C lower than the ambient temperature.

[0093] It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various changes or modifications within the scope of the claims, which do not affect the essence of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments may be combined with each other at will.

Claims

1. A radiant heat dissipation coating, characterized in that: It is prepared from the following raw materials including the following components and parts by weight: 4-15 parts of functional filler; 1 part of adhesive; 5-100 parts of solvent.

2. The radiant heat dissipation coating according to claim 1, characterized in that: The functional filler comprises diatomaceous earth, and the particle size of the diatomaceous earth is 1-15 μm and the pore size is 10-500 nm.

3. The radiant heat dissipation coating according to claim 2, characterized in that: The functional filler also includes one or more of calcium carbonate, barium sulfate, titanium dioxide, silicon dioxide, and aluminum oxide.

4. The radiant heat dissipation coating according to claim 1, characterized in that: The binder includes methylcellulose.

5. The method for preparing the radiant heat dissipation coating according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, sintering the functional filler at high temperature; S2, adding a binder to a solvent and stirring to obtain a solution; S3, adding the functional filler into the solution in step S2; S4. After stirring and removing bubbles, the radiant heat dissipation coating is obtained.

6. The preparation method according to claim 5, characterized in that: The high temperature sintering method in step S1 includes: high temperature sintering, the sintering temperature is 450-1200° C., and the sintering time is 4-12 hours.

7. The preparation method according to claim 5, characterized in that: The stirring method in step S2 includes magnetic stirring, with a rotation speed of 400-1300 r / min and a stirring time of 4-12 h.

8. The preparation method according to claim 5, characterized in that: The mass ratio of the binder to the solvent in step S2 is 1:5-100, and the mass ratio of the functional filler to the binder in step S3 is 4-15:

1.

9. The preparation method according to claim 5, characterized in that: After adding the functional filler into the solution in step S2 in step S3, stirring is further performed. The stirring method includes magnetic stirring, the rotation speed is 500-1300 r / min, and the stirring time is 1-12 h.

10. The preparation method according to claim 5, characterized in that: The stirring and defoaming method in step S4 includes using a centrifugal defoaming mixer for stirring and defoaming, the rotation speed of the centrifugal defoaming mixer is 1000-2000 rpm, and it runs in a stirring mode for 5-20 minutes and a defoaming mode for 5-20 minutes respectively.

Citation Information

Patent Citations

  • EVA adhesive film surface nano paint

    CN103555040A

  • Paint with strong adhesion for cooling surface for LED (light emitting diode) radiator

    CN103965672A

  • Color reflection heat insulation and temperature reduction paint and preparation method thereof

    CN106634349A

  • Calcined diatomite non-expandable fire-proof coating

    CN106752143A

  • Passive radiation refrigeration composite material layer and preparation method thereof

    CN111393915A